The World Bank Group’s Support to Capital Market Development - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This evaluation assesses the World Bank Group’s contributions towards capital market development in client countries. It examines the activities the Bank Group has in all segments of capital market development, both in the public and private sectors, including interventions across 64 countries. It draws conclusions on the Bank Group’s strategic approach to capital markets, on the coordination across program areas, on the sequencing and clustering of reforms and on adapting advice to country and global needs. The report does not attempt to holistically cover all potential sources of long term development finance, and has limited itself to capital markets finance only. These areas are still to be evaluated.